THE AVOIDABLE WAR The Dangers of a Catastrophic Conflict between the US and Xi Jinping's China - Rudd, Kevin (PublicAffairs, 2022)
A war between China and the US would be catastrophic, deadly, and destructive. Unfortunately, it is no longer unthinkable. The relationship between the US and China, the world's two superpowers, is peculiarly volatile. It rests on a seismic fault--of cultural misunderstanding, historical grievance, and ideological incompatibility. No other nations are so quick to offend and be offended. Their militaries play a dangerous game of chicken, corporations steal intellectual property, intelligence satellites peer, and AI technicians plot. The capacity for either country to cross a fatal line grows daily.